A hybrid non-gray gas radiation heat transfer solver based on OpenFOAM. (April 2022) - Sun, Yujia; Shen, Haomin; Zheng, Shu; Jiang, Lin
Highlights: OpenFOAM based non-gray gas radiation solvers are developed. DOM and P1 are used to solve different gray gases in the WSGG. Validations proves the capablility of the developed model. Abstract: Radiation heat transfer is important in many combustion conditions. Efficient and accurate predictions of the radiation energy is essential for numerical simulation of combustion. A hybrid non-gray gas radiation solver is developed based on the open-source OpenFOAM framework. The weighted-sum-of-gray-gases (WSGG) model is used for the non-gray gas radiative properties. The discrete ordinates method (DOM) and first order spherical harmonics (P1) method are adopted to solve the different gray gas RTEs in the WSGG model. The performance of the hybrid solver is analyzed in detail for three cases. Results show that the accuracy of the hybrid solver decreases with increasing the number of gray gases solved by the P1 method, while the computational time increases. The advantage of the hybrid solver is more obvious in isotherm and homogenous cases, in which the relative mean errors in terms of radiative heat flux and heat source can be less than 5% while reducing half of the computational time.